Navigating the cholera elimination roadmap in Zambia - A scoping review (2013-2024). - Nyuma Mbewe; John Tembo; Mpanga Kasonde; Kelvin Mwangilwa; Paul Msanzya Zulu; Joseph Adive Sereki; William Ngosa; Kennedy Lishipmi; Lloyd Mulenga; Roma Chilengi; Nathan Kapata; Martin Peter Grobusch (PLoS Neglected Tropical Diseases, 2025)
Background Cholera outbreaks are increasing in frequency and severity, particularly in Sub-Saharan Africa. Zambia, committed to ending cholera by 2025, instead experienced its most significant outbreak in 2024. This review examines the perceived regression in elimination efforts by addressing two questions: (i) What is known about cholera in Zambia? and (ii) What are the main suggested mechanisms and strategies to further elimination efforts in the region?. Methodology/principal findings A scoping literature search was conducted in PUBMED to identify relevant qualitative and quantitative research studies published between 1st January 2013 and 30th June 2024 using the search terms 'cholera' and 'Zambia'. We identified 53 relevant publications. With the increasing influence of climate change, population growth, and rural-urban migration, further increases in outbreak frequency and magnitude are expected. Risk factors for recurrent outbreaks, including poor access to water, sanitation, and hygiene (WASH) services in unplanned urban settlements and rural fishing villages, continue to derail elimination efforts. Interventions are best planned at a decentralised, community-centric approach to prevent elimination and reintroduction at the district level. Pre-emptive vaccination campaigns before the rainy season and climate-resilient WASH infrastructure in cholera hotspots are also recommended. Conclusions/significance The goal to eliminate cholera by 2025 was unrealistic, as evidence points to the disease becoming endemic. Our findings confirm the need to align health and WASH investments with the Global Roadmap to Cholera Elimination by 2030 through a climate-focused lens. Recommendations for cholera elimination, including improved access to safe drinking water and sanitation, remain elusive in many low-income settings like Zambia. Patient-level information on survival and transmissibility is lacking. New research tailored to country-level solutions and enhancing community participation is urgently required. Insights from this review will be integrated into the next iteration of the National Cholera Control Plan and could apply to other countries with similar settings.